Bioinsecticide effect of Metarhizium anisopliae on termite pests Microtermes lepidus and Psammotermes hybostoma in the laboratory - Sonko, Arfang Mafoudji; Sall, Dienaba; Ndiaye, Mouhamadou Moustapha; Ndiaye, Abdoulaye Baïla (European Scientific Journal, ESJ, 2025)
In Senegal, several studies have shown the economic importance of termite damage to crops. Farmers use chemical methods that are dangerous for humans, animals, crops, soil, and environmental health. Thus, the use of entomopathogenic fungi would be an effective and environmentally eco-friendly alternative to chemical pesticide use. The objectives of this study are to i) carry out infestations in the laboratory, ii) determine the lethal time (TL50) and iii) observe the germination of spores on the corpses of these species. The methodology is based on i) the infestation of 10 workers of Microtermes lepidus and Psammotermes hybostoma with Metarhizium solutions, ii) the monitoring of mortalities, iii) the determination of the lethal time 50 (LT50) and iv) germination of spores on corpses. For the determination of LT50, the concentrations of 1 g/L and 1.5 g/L gave an LT50 of less than one day in workers of Microtermes lepidus and Psammotermes hybostoma. For the concentration of 0.5 g/l, the LT50 is 2.5 days for workers of Psammotermes hybostoma and less than one day for those of Microtermes lepidus. Incubation revealed the appearance of spores on the cadavers, which were given a concentration of 0.5 g/l. This study shows that mortality is related to the concentration of the solution. The higher the concentration, the shorter the LT50 time. The bioinsecticidal effect of Metarhizium anisopliae is not immediate, resulting in an LT50 of 1 to 2 days depending on the species.